2019
DOI: 10.4094/chnr.2019.25.1.65
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with Maternal Attachment of Breastfeeding Mothers

Abstract: This study aimed to identify factors associated with maternal attachment of breastfeeding mothers, with a focus on the mothers' breastfeeding characteristics. Methods: Data were collected from 217 mothers who breastfed their healthy baby for 1 month after childbirth and had no postpartum complications. The data were analyzed by hierarchical regression analysis. Results: The factors significantly associated with maternal attachment were an emotional exchange with one's baby (β=.41, p<.001), breastfeeding confid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 25 publications
0
10
0
1
Order By: Relevance
“…However, this motivation was contingent on breastfeeding being compatible with their lives. Furthermore, previous research has found that motivation to continue breastfeeding is contingent on the infant's response and satisfactory interaction (Kim, 2019), so it might be beneficial to reinforce the positive emotions that foster the feeling of attachment (Kim, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…However, this motivation was contingent on breastfeeding being compatible with their lives. Furthermore, previous research has found that motivation to continue breastfeeding is contingent on the infant's response and satisfactory interaction (Kim, 2019), so it might be beneficial to reinforce the positive emotions that foster the feeling of attachment (Kim, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Longer duration of breastfeeding may promote maternal attachment, specifically maternal response to the infant, maternal sensitivity, and maternal ability to read the infant's cues 7. Breastfeeding positively correlates with maternal bonding 23…”
Section: Breastfeedingmentioning
confidence: 99%
“…21 The nonlactating mother is more likely to experience postpartum depression (PPD) (or vice versa), with exclusive breastfeeding correlating with lower likelihood of depressive symptoms. [22][23][24] Especially when paired with limited social support and increased stress levels, the discontinuation of exclusive breastfeeding is associated with signifi cantly higher odds of PPD. 22 Longer duration of breastfeeding may promote maternal attachment, specifi cally maternal response to the infant, maternal sensitivity, and maternal ability to read the infant's cues.…”
Section: Health Benefi Ts For the Lactating Parentmentioning
confidence: 99%
See 1 more Smart Citation
“…However, Whitley et al (2020) found no or weak association in oxytocin between depressed or anxious women six months postpartum Recently, Miller-Graff and Scheid (2020) investigated the complex relationship between IPV, mental health and EBF and suggested a moderating effect of breastfeeding at six weeks after childbirth with prenatal IPV exposure. As such, the next generation of birth cohort studies could further investigate the complex factors related to EBF and effects of p-IPV on mother-infant attachment and maternal psychological functioning on the lactation process (Kim, 2019).…”
Section: Exclusive Breastfeeding: Intention Vs Practicementioning
confidence: 99%